Nutritional quality of beverages available in vending machines in health and social care institutions: do we really want such offers? - Urška Rozman; Nataša Fidler Mis; Urška Pivk Kupirovič; Igor Pravst; Primož Kocbek; Maja Strauss; Sonja Šostar Turk (BMC, 2021)
Abstract Background Vending machines represent one way of offering food, but they are overlooked in the efforts to improve people's eating habits. The aim of our study was to analyse the variety and nutritional values of beverages offered in vending machines in social and health care institution in Slovenia. Methods The available beverages were quantitatively assessed using traffic light profiling and the model for nutrient profiling used by Food Standards Australia New Zealand. Vending machines in 188 institutions were surveyed, resulting in 3046 different beverages consisting of 162 unique product labels. Results Between 51 and 54% of beverages were categorised as unhealthy with regard to sugar content. Water accounted for only 13.7% of all beverages in vending machines. About 82% of beverages in vending machines were devoted to sugar-sweetened beverages, the majority (58.9%) presented in 500-ml bottles. The average sugar content and average calories in beverages sold in vending machines are slightly lower than in beverages sold in food stores. Conclusions We suggest that regulatory guidelines should be included in the tender conditions for vending machines in health and social care institutions, to ensure healthy food and beverage choices.